VRTeaching: a tool for virtual reality remote lectures - Florian Glawogger; Michael Holly; Janine Tasia Stang; Hanna Schumm; Fabia Lang; Emil Criscione; Jack Dennis Pham; Verena Wagner-Hartl; Johanna Pirker (Frontiers in Education)
IntroductionRemote teaching often feels unnatural and restricted compared to on-site lectures, as traditional teaching aids are reduced to a 2D interface. The increasing adoption of VR expands online teaching platforms by offering new possibilities for educational content and enables teachers to teach more intuitively. While the potential of virtual reality (VR) for learners is well-investigated in the academic literature, VR tools for educators have hardly been explored. In this paper, we introduce the tool VRTeaching, a platform designed for presenters to enable immersive lectures using VR glasses and integrated tools such as an interactive whiteboard that can display slides, built-in chat integration to enable communication, and interactivity features such as polling tools or audience questions.MethodsThe presented study includes an expert evaluation assessing the usability and the potential of the teaching and learning platform and an investigation of the mental demand and psychophysiological responses on teachers and students giving presentations depending on the teaching environment.ResultsThe results indicate a significantly higher mental demand for the VR environment than the online environment, with no significant effects on the psychophysiological measures.DiscussionDespite the increased perceived mental demand, participants recognized the VR lecture room as having strong potential for enhancing teaching and learning experiences. These findings highlight the potential of VR-based platforms for remote education while underlining the importance of considering cognitive load aspects in their design.